Ligurian leafhopper Eupteryx decemnotata (Rey) (Insecta: Hemiptera: Cicadellidae: Typhlocybinae) - Alexander Tasi; Andrea Lucky (EDIS, 2020)
The Ligurian leafhopper, Eupteryx decemnotata (Rey), is an insect in the family Cicadellidae that has undergone a rapid range expansion in the last three decades. It is a potential pest of plants in the mint family (Lamiaceae), and its spread may be assisted by the commercial transportation of its host plants.